Strategi Pengelolaan Sampah Rumah Tangga: Solusi Alternatif bagi Pemerintah Kota Kupang - Irmasari Welhelmina Nenobais (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2021)
As far as one can see, the problem of handling and reducing waste in Kupang City seems to be only a burden and responsibility of The Regional Government through The Kupang City Environment and Hygiene Service. However, basically, the problem of urban waste is a shared responsibility between the community and the government, which requires active role of the community in alleviating the problem. So far, it has not been maximized due to the community's dependence on the local government's action program for the existing problems. The fact that there has not been a paradigm shift, namely the attitude and awareness of the community to manage waste resources, has become a problem in itself. For this reason, alternative solutions are needed, in the form of EPR policies, Fiscal Incentives and Circular Economics to bridge the dilemma that arises as a result of the lack of awareness and apathetic behavior of the community regarding the problem of urban waste.